Inhibition of p38 mitogen activated protein kinase activation and mutant SOD1G93A-induced motor neuron death - Maarten Dewil (Neurobiology of Disease, 2007)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by the selective loss of motor neurons. Stress activated protein kinases (SAPK) have been suggested to play a role in the pathogenesis of ALS. We studied the relevance of p38 MAPK for motor neuron degeneration in the mutant SOD1 mouse. Increased levels of phospho-p38 MAPK were present in the motor neurons and microglia of the ventral spinal cord. The p38 MAPK-inhibitor, SB203580, completely inhibited mutant SOD1-induced apoptosis of motor neurons and blocked LPS-induced activation of microglia. Semapimod, a p38 MAPK inhibitor suitable for clinical use, prolonged survival of mutant SOD1 mice to a limited extent, but largely protected motor neurons and proximal axons from mutant SOD1-induced degeneration. Our data confirm the abnormal activation of p38 MAPK in mutant SOD1 mice and the involvement of p38 MAPK in mutant SOD1-induced motor neuron death. We demonstrate the effect of p38 MAPK inhibition on survival of mutant SOD1 mice and reveal a dissociation between the effect on survival of motor neurons and that on survival of the animal, the latter likely depending on the integrity of the entire motor axon.